Qeco-Quantitative ecology software: A collaborative approach - Pla, Laura; Di Rienzo, Julio A.; Casanoves, Fernando; Vilchez, Sergio; Di Rienzo, Mauricio J.; Romero, María del Carmen (2021)
Qeco is a statistical software for analysis of ecological data. It has a simple and user-friendly interface that makes the difference in the experience of data analysis. It implements state-of-the-art statistical and quantitative ecological methods. The principal characteristic that makes it different is that it not only merges the best of the ease-to-use menu-driven software with the power of R, but that it can growth according to the needs and knowledge of the users. This is possible because Qeco creates an interface that allows the users to add new menus and menus items according to her/his needs including helps and test data. The ecological community will benefit from the collaborative efforts of its members which will make, Qeco, their main companion for data analysis and interpretation.